Characteristics and functional outcomes of brain injury caused by physical assault in Canada: a population-based study from an inpatient rehabilitation setting. (December 2013) - Kim, Hwan; Bayley, Mark; Dawson, Deirdre; Mollayeva, Tatyana; Colantonio, Angela
Abstract Purpose: To investigate the characteristics and inpatient rehabilitation outcomes of persons who sustained a traumatic brain injury (TBI) resulting from physical assault – a form of intentional TBI – and compare these outcomes to those of persons with TBI resulting from other aetiologies. Method: A prospective population-based cohort study using inpatient rehabilitation data from Canadian population-based administrative databases for the fiscal years 2001–2006. Outcome measures were measures of functional independence (motor and cognitive), as measured by the FIM™ Instrument, and discharge destinations. Results: Characteristics associated with intentional TBI were being male, younger in age and unemployed; living alone and having a greater likelihood of alcohol/drug abuse prior to admission. The intentional TBI group showed poorer total functional gains at discharge from inpatient rehabilitation. Multivariate regression analyses showed that persons with intentional injury were less likely to be discharged home. Conclusions: Persons with TBI from physical assault are a distinct clinical group in Canadian inpatient rehabilitation settings. These findings can support clinicians in determining proper assessment, management, discharge planning and post-rehabilitation care that target specific needs of persons with TBI resulting from physical assault. Implications for Rehabilitation Clinicians should have appropriate training to properly assess the mental health status of this patient group. Inpatient rehabilitation facilities should be prepared to provide services targeting psychosocial, substance abuse and interpersonal relationship issues to persons with a TBI from physical assault while patients are still within a hospital setting. Follow-up clinical care and community support services are warranted for those with intentional TBIs, including provision of occupational rehabilitation services, such as vocational rehabilitation. The discharge team should be responsible for ensuring appropriate discharge to community in the absence of family or other advocates on behalf of the patient.